One Bullet Causing Five Holes, Laparoscopic Exploration with Repair: A Case Report and Review of the Literature. (3rd August 2020) - Jones, Hunter; Ahmed, Hassan
Abstract : Introduction . The proper treatment of penetrating abdominal wounds has been a controversial topic, and the preferred regimen has evolved over time. In recent years, many trauma centers have started using diagnostic laparoscopy in stable trauma patients in an effort to reduce the incidence of nontherapeutic laparotomy. This is more commonly seen in solid organ injuries, and its role is less clearly defined for hollow visceral injuries. Case Presentation . A 19-year-old male presented with a gunshot wound (GSW) to the abdomen with mild peritoneal signs and computed tomography (CT) findings. Diagnostic laparoscopy was performed with the repair of five lacerations to intra-abdominal organs including the sigmoid colon, rectum, bladder, and small bowel. Discussion . To our knowledge, this is the first case report in the literature detailing such a GSW repair. Abdominal GSWs have been repaired laparoscopically in the past, but none have elaborated on the repair of multiple defects of bowel and/or bladder. Conclusion . Therapeutic laparoscopy can be considered in selected cases of penetrating abdominal trauma. Laparoscopy offers several advantages over laparotomy including decreased mortality, complication rate, and length of stay.